Identifying Quality Factors for Self-Tracking Solutions: A Systematic Literature Review - Schiller, Barbara; Brogt, Tobias; Schuler, J. Peter M.; Strobel, Gero; Eicker, Stefan (Proceedings of the 53nd Hawaii International Conference on System Sciences, 2020)
Self-tracking solutions have become globally widespread, as they promise numerous advantages (e.g. improving health) to their users. Despite their benefits, such solutions are often abandoned due to quality issues. This phenomenon can also be observed for digitized products in general. As self-tracking solutions are hybrid products, combining digital and physical components, traditional domain-independent and abstract quality models like the prominent ISO 25000 standard seem to not cover quality in an appropriate way. We address these issues by answering the research question of which factors affect quality perceptions of different stakeholder groups when interacting in a wearable ecosystem. We use a systematic literature review based on a research protocol to identify and analyze 98 quality-influencing factors from 19 studies that we cluster in a map. The identified factors are compared to the ISO 25000 standard, showing that certain factors like hedonic motivation are unconsidered thoroughly in the existing standard.